An Analysis of The Cost Efficiency in Australian Banking Sector Pre and Post Global Financial Crisis - Wu, Zhaozhou (2014)
This paper analysis the cost efficiency of banks in Australia from 1999 to 2013, pre and posts the global financial crisis. The analysis is carried out on a sample of 104 Australian banks including ‘Big Four’, regional and foreign banks. The measurement of cost efficiency is done through stochastic frontier analysis. Two specifications of models have been built to imply how efficiency levels vary with different inputs and outputs. The cost efficiency scores before and post the global financial crisis are measured separately. The study shows that the average cost efficiency score of Australian banks is lower than the world mean indicates that there is a need for them to cut their cost and further improve efficiency in order to accomplish world best practice. In addition, the slightly decrease of cost efficiency after the global financial crisis indicates that the crisis have adverse but limited effect on Australian banks. The results provide useful implications to bank mangers, investors, creditors and depositors in evaluating the performance of banks so as to better manage their investments. Also, this study provides some signals and implications for regulators to adjust and set a safe and soundness financial system in Australia.